Cerebellar Symptoms Are Associated With Omission Errors and Variability of Response Time in Children With ADHD. (February 2017) - Goetz, Michal; Schwabova, Jaroslava; Hlavka, Zdenek; Ptacek, Radek; Zumrova, Alena; Hort, Vladimír; Doyle, Robert
Objective: We examined the presence of cerebellar symptoms in ADHD and their association with behavioral markers of this disorder.Method: Sixty-two children with ADHD and 62 typically developing (TD) children were examined for cerebellar symptoms using the ataxia rating scale and tested using Conners' Continuous Performance Test.Results: Children with ADHD had significantly more cerebellar symptoms compared with the TD children. Cerebellar symptom scores decreased with age in the ADHD group; in the TD group remained stable. In both groups, cerebellar symptoms were associated with parent-rated hyperactive/impulsive symptoms, variability of response time standard error (RT-SE) and increase of RT-SE as the test progresses. More variables were associated with cerebellar symptoms in the ADHD group including omission errors, overall RT-SE and its increase for prolonged interstimulus intervals.Conclusion: Our results highlight the importance of research into motor functions in children with ADHD and indicate a role for cerebellar impairment in this disorder.